Chemical Composition of Essential Oils Obtained from Heteromorpha arborescens (Spreng.) Cham. and Schltdl Leaves Using Two Extraction Methods - Taiwo Oluwafunmilola Abifarin; Gloria Aderonke Otunola; Anthony Jide Afolayan (The Scientific World Journal)
This study was aimed at comparing the essential oils obtained from Heteromorpha arborescens leaves by Solvent-Free Microwave Extraction (SFME) and Hydrodistillation (HD) methods in terms of their chemical compositions, yield, CO2 emission, and energy consumption. The solvent-free microwave extraction method indicated a higher oil yield of 0.7 mL/200 g (0.35%) as compared to 0.59 mL/200 g (0.295%) obtained through hydrodistillation. GC-MS analysis of the oils revealed a total of 52 chemical components from both methods with the presence of 35 (96.52%) and 30 (71.15%) chemical constituents for HD and SFME, respectively. The major constituents observed in the essential oil extracted by SFME methods include α-pinene (6%), D-limonene (11.27%), β-ocimene (9.09%), β-phellandrene (6.33%), β-mycene (8.49%), caryophyllene (5.96%), and camphene (4.28%). However, in the hydrodistillation method, the oil was majorly composed of a-pinene (4.41%), β-pinene (10.68%), β-ocimene (6.30%), germacrene-D (5.09%), humulene (5.55%), and α-elemene (6.18%). The SFME method was better in terms of saving energy (0.25 kWh against 4.2 kWh of energy consumed), reduced CO2 emission (200 g against 3360 g of CO2), a higher yield, and better quality of essential oil due to the presence of higher valuable oxygenated compounds (8.52%) against that of the hydrodistillation method (2.96%). The SFME method is, therefore, a good alternative for extracting the oils of H. arborescens leaves since the essential oil yield is higher with more oxygenated compounds, considerable energy savings, lower cost, and reduced environmental burden at substantially reduced extraction time (30 min as opposed to 180 min).